Innovative Practice and Management Extracurricular Education System: Distance Technologies in Non-Formal Project-Based Learning - Kosarikov, Alexander N.; Davydova, Natalia G. (International Journal of Management Innovation Systems, 2024)
The paper describes the innovative system of the extracurricular project-based education program of high school students, combined with the national contest of research projects carried out in the learning process. This system is developed and managed in the format of a Society-State-Private partnership as an attempt to adapt education to post-industrial development. The organization of extracurricular education in the form of a public-state partnership facilitates long-distance interactions between the individual students and student teams, and the groups of researchers and experts. Such interactions enable the peer-to-peer methods in education; the high school students learn the integrated STEM approaches to project implementation (PI). At the same time, utilization of the hybrid education methods preserves the emotional atmosphere of scientific cooperation during PI. The extracurricular project-based learning used in our system allows students to adjust quicjly the acquired skills to dynamic changes in technology and management over the transition to post-industrial development. Utilization of Information and Communication Technologies (ICT) meets the goals of operative adaptation of the subject matter and education methods to the evolving realities of post-industrial societies, and preserves the integrity and synchronicity of education process within the spatially distributed structures of our extracurricular learning system. ICT utilization within our system of the extracurricular program combines the project-based learning with the organization of the national contest of students’ projects and facilitates cross-disciplinary approach to PI that motivates the students towards sustainability goals attainment.